Transition From Childhood to Adult Care in Patients with Type 1 Diabetes: 20 Years of Experience From the Tübinger Transition Study - Schweizer, Roland; Lösch-Binder, Martina; Hayn, Clara; Friz, Silas; Uber, Julia; Ziegler, Julian; Liebrich, Franziska; Neu, Andreas (Experimental and Clinical Endocrinology & Diabetes, 2023)
Aims Transition from pediatric to adult care is difficult for patients with chronic diseases. In this study, factors associated with metabolic control in childhood-onset type 1 diabetes (T1D) after transfer to adult care were analyzed.Methods Overall, 224 persons with T1D were contacted yearly from 1998 to 2019. They voluntarily answered a questionnaire about their current hemoglobin A1c (HbA1c) levels, diabetes-associated complications, kind of care, living conditions, and family situation. Then, mixed longitudinal-cross-sectional analyses were carried out.Results Overall, 190 patients answered at least once (mean age: 26.6 years). Diabetes complications were mentioned by 10 patients (5 microalbuminuria, 5 retinopathy). Most patients (92.6%) were in diabetes-specific care during the first year after transfer, with a trend to leave diabetes-specific care during the observation period. Patients in diabetes-specific care displayed lower HbA1c levels (%/mmol/mol) (7.1/54 vs. 7.5/58). An important predictor for HbA1c after transfer was HbA1c during the year before transfer (r=0.67, p <0.001). Patients living alone showed no difference in HbA1c levels from those living with their parents. Married patients had lower HbA1c levels (7.0/53 vs. 7.3/56, p<0.05) than unmarried ones. Patients with children (15.8%) presented lower HbA1c levels (6.9/52 vs. 7.3/56, p <0.01) than those without.Conclusions Good metabolic results are favored in patients followed-up in specialized care, are married, and are parents. We recommend transfer to a diabetologist with experience in T1D at an individual age.
Keywords: diabetes care; type 1 diabetes; diabetic control; family situation; HbA1c; transition